Production, purification, and characterization of recombinant hFSH glycoforms for functional studies - Butnev, Viktor Y. (Mol Cell Endocrinol, 2015)
Previously, our laboratory demonstrated the existence of a β-subunit glycosylation-deficient human FSH glycoform, hFSH(21). A third variant, hFSH(18), has recently been detected in FSH glycoforms isolated from purified pituitary hLH preparations. Human FSH(21) abundance in individual female pituitaries progressively decreased with increasing age. Hypo-glycosylated glycoform preparations are significantly more active than fully-glycosylated hFSH preparations. The purpose of this study was to produce, purify and chemically characterize both glycoform variants expressed by a mammalian cell line. Recombinant hFSH was expressed in a stable GH(3) cell line and isolated from serum-free cell culture medium by sequential, hydrophobic and immunoaffinity chromatography. FSH glycoform fractions were separated by Superdex 75 gel-filtration. Western blot analysis revealed the presence of both hFSH(18) and hFSH(21) glycoforms in the low molecular weight fraction, however, their electrophoretic mobilities differed from those associated with the corresponding pituitary hFSH variants. Edman degradation of FSH(21/18) -derived β-subunit before and after peptide-N-glycanase F digestion confirmed that it possessed a mixture of both mono-glycosylated FSHβ subunits, as both Asn(7) and Asn(24) were partially glycosylated. FSH receptor-binding assays confirmed our previous observations that hFSH(21/18) exhibits greater receptor-binding affinity and occupies more FSH binding sites when compared to fully-glycosylated hFSH(24). Thus, the age-related reduction in hypo-glycosylated hFSH significantly reduces circulating levels of FSH biological activity that may further compromise reproductive function. Taken together, the ability to express and isolate recombinant hFSH glycoforms opens the way to study functional differences between them both in vivo and in vitro.